Structural Solutions that Increase the Dynamic Accuracy of a Wave Solid-State Gyroscope - D. M. Malyutin (Приборы и методы измерений)
The development of wave solid-state gyroscopes (VTG) is one of the promising areas of development of gyroscopic angular velocity sensors. VTG from the standpoint of manufacturing technology, tuning and control systems, as well as accuracy characteristics, has a number of advantages compared to other types of gyroscopes. When developing VTG, they strive to reduce the gyroscope's own care, zero signal bias, and the non-linearity of the scale factor in the operating temperature range However, when creating the device, due attention is often not paid to the existing opportunities to improve the dynamic accuracy of the gyroscope by developing promising structural solutions for building control circuits and information processing. The solution to this problem was the goal of the work.Using the methods of the theory of automatic control, the dynamics of a wave solid-state gyroscope with a metal resonator and piezoelectric elements in the closed-loop mode of Сoriolis acceleration compensation are studied. Piezoelectric elements perform the functions of displacement and force sensors.Two promising structural solutions for constructing VTG control and information processing circuits are proposed and considered. Relations are established for selecting the parameters of the links of these contours, which provide an increase in the dynamic accuracy of the gyroscope. In the first case, the proposed structure for constructing the VTG allows us to significantly reduce the dynamic errors caused by the difference in the scale coefficient of the VTG at different frequencies of the measured angular velocity in the bandwidth. Such a structure for constructing a VTG can be recommended when solving a measurement problem in which it is necessary to accurately measure the angular velocity, and the phase lag of the output signal in relation to the measured angular velocity is of secondary importance. In the second case, the proposed structure of the VTG construction corresponds to the transfer function of the relative measurement error with secondorder astatism, and the absolute measurement error in the frequency band of 10 Hz does not exceed 0.1 %.